Odpowiedzi

2010-01-25T17:29:54+01:00
Jeśli dobrze zrozumiałam zadanie powinno być tak :

A) -4x - 7 - 3x + 7 = -4x - 3x = 7 - 7
- 7x = 0

B) x-2xy+½x-⅓x=
x + 1/2x - 1/3x = 2xy
1,5 x - 1/3x = 2xy

C)-x²+y²-2x²-2y²=
-x² - 2x² = -y²+ 2y²
- 3x² = y²

D)-x²+2x-3x+x²=
- x² + x² = 3x - 2x
0 = x

E)4x+4-7x-½=
4x - 7x = -4 + 1/2
- 3x = -3,5

F)-2ab+12a-4ab-16a=
- 2ab - 4ab = 16a - 12a
-6ab = 4a
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-01-25T17:31:57+01:00
A)-4x-7-3x+7=-7x
B)x-2xy+½x-⅓x=6/6x-2xy+3/6x-2/6x=7/6x-2xy=x(7/6-2y)
C)-x²+y²-2x²-2y²=-3x²-1y²
D)-x²+2x-3x+x²=-3x
E)4x+4-7x-½=-3x+3 1/2
F)-2ab+12a-4ab-16a=-6ab-4a=2a(-3b-2)